Comparing the spectral profiles of the javanesse gending with the classical music as the therapeutical music - Nurida Finahari; Gatut Rubiono; Gatot Soebiyakto (Biomedical Engineering, 2016)
Objective: So this study is trying to analyze the potency of Javanesse Gending as the therapeutic music. It is a further exploration of the finding state that the Gending Tejanatha has the spectral characteristic similarity with The Magic Flute of Mozart. Material and methods: The study was done by analyze the audio characteristics patterns of five Javanesse Gending (JG) compare with the five classical music (CM) of Mozart and Beethoven. The audio characteristics were obtained from the sound analyzer program. The results were in form of spectral graphics. The parameters include spectral envelope, sound intensity and frequency.Result: JG and CM have different pattern for the left and the right audio. This indicate difference stimulus for the neural, that will appear as cross references for primary audiory area. The frequencies of JG is higher than CM. The frequency and envelope indicate the variation of emotion that will be induced. It represent the sound colour (timbre). The JG timbre is determined by the material of the instruments, used to made from copper or iron. This material does infuence the emotional responses, especially to the player (pengrawit). The influence of the timbre, not as intens as the influence of the musical tempo that relate with the rhythm harmony. In the JG, the musical tempo represent the soul of this music. It is very essential. The tempo changes from the usual pattern will raise the anxiety.Conclusion: It can be concluded that the JG has the same potency as the CM to be used as therapeutic music. The JG has the higher potency to influence emotional state than the CM due to its envelope profile.